Aromatic polyamide nonporous membranes for gas separation application - Bera Debaditya (De Gruyter, 2021)
Polymer membrane-based gas separation is a superior economical and energy-efficient separation technique over other conventional separation methods. Over the years, different classes of polymers are investigated for their membrane-based applications. The need to search for new polymers for membrane-based applications has been a continuous research challenge. Aromatic polyamides (PAs), a type of high-performance materials, are known for their high thermal and mechanical stability and excellent film-forming ability. However, their insolubility and processing difficulty impede their growth in membrane-based applications. In this review, we will focus on the PAs that are investigated for membrane-based gas separations applications. We will also address the polymer design principal and its effects on the polymer solubility and its gas separation properties. Accordingly, some of the aromatic PAs developed in the authors’ laboratory that showed significant improvement in the gas separation efficiency and placed them in the 2008 Robeson upper bound are also included in this review. This review will serve as a guide to the future design of PA membranes for gas separations.